2023
DOI: 10.3389/fimmu.2023.1209874
|View full text |Cite
|
Sign up to set email alerts
|

Novel mediator in anaphylaxis: decreased levels of miR-375-3p in serum and within extracellular vesicles of patients

Emilio Nuñez-Borque,
Sergio Fernandez-Bravo,
Pablo Rodríguez Del Rio
et al.

Abstract: IntroductionAnaphylaxis is among the most severe manifestations of allergic disorders, but its molecular basis remains largely unknown and reliable diagnostic markers are not currently available. MicroRNAs (miRNAs) regulate several pathophysiological processes and have been proposed as non-invasive biomarkers. Therefore, this study aims to evaluate their involvement in anaphylactic reaction and their value as biomarkers.MethodsAcute (anaphylaxis) and baseline (control) serum samples from 67 patients with anaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The 10 samples evaluated by next-generation sequencing (NGS) from each group of patients were analyzed in the same batch and under identical conditions. In turn, in previous studies ( 20 , 21 ), we confirmed the correct performance of the NGS by analyzing different quality controls.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The 10 samples evaluated by next-generation sequencing (NGS) from each group of patients were analyzed in the same batch and under identical conditions. In turn, in previous studies ( 20 , 21 ), we confirmed the correct performance of the NGS by analyzing different quality controls.…”
Section: Methodssupporting
confidence: 81%
“…In the allergy field, most of the research has focused special attention elucidating the role of miRNA and lncRNA, particularly those carried by extracellular vesicles (EVs) ( 28 32 ). Specifically, differential profiles of miRNAs in children with food-mediated anaphylaxis and adults with drug-mediated anaphylaxis have already been described by our group ( 20 , 21 ). However, the possible involvement of the other sncRNA is practically unexplored.…”
Section: Discussionmentioning
confidence: 66%